Minimality and Sylow-Permutability in Locally Finite Groups - Robinson, D. J. S. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We give a complete classification of the locally finite groups that are minimal with respect to Sylow-permutability being intransitive.